Infliximab for Anoperineal Lesions in Crohn's Disease: Remission Appears to be Based on Rapid Combination Therapy at High Doses - Nadia Fathallah; Cosmin Cristea; Hélène Beaussier; Sonia Khirani; Vincent de Parades (Journal of Coloproctology, 2022)
Study Aim The aim of the present study was to compare in real life the characteristics of treatment with infliximab according to the presence or absence of anoperineal involvement in Crohn's disease. Methods We performed a single-center, prospective, non-interventional study, on patients with Crohn's disease in remission who had been treated with infliximab for at least 1 year. Patients with poor treatment compliance, on antibiotics, or those with a stoma were excluded. Results We included 52 patients in this study: 34 with anoperineal lesions with or without luminal lesions, and 18 with luminal lesions only. Patients with anoperineal lesions were more likely to have undergone surgery (70.6% versus 38.9%, p = 0.027), had a shorter median time to infliximab treatment initiation (0.5 versus 5.5 years, p = 0.005), a higher mean dose of infliximab (6.6 versus 5.1 mg/kg, p = 0.015), and were more likely to receive combination treatments including infliximab (52.9% versus 11.1%, p = 0.008) than patients with luminal involvement only. Conclusions In our study, infliximab treatment was initiated more quickly, at higher doses, and more in combination therapy for anoperineal Crohn's disease than for luminal damage alone. Additional studies are required to confirm this finding and to assess the tolerance of this treatment throughout patient management.